Use of hemodynamic and laboratory monitoring tools to reduce the risk of mortality from pediatric septic shock - Saptadi Yuliarto; Kurniawan Taufiq Kadafi; Ika Maya Suryaningtias; Irene Ratridewi; Savitri Laksmi Winaputri (Paediatrica Indonesiana, 2023)
Background Early recognition of septic shock in terms of clinical, macrocirculatory hemodynamic, and microcirculatory laboratory parameters is a fundamental challenge in the emergency room and intensive care unit for early identification, adequate management, prevention of disease progression, and reduction of mortality risk. Objective To evaluate for possible correlations between survival outcomes of post-resuscitation pediatric septic shock patients and parameters of clinical signs, macrocirculatory hemodynamics, as well as microcirculatory laboratory findings. Methods This prospective, study was conducted in the PICU at Saiful Anwar Hospital, Malang, East Java. Inclusion criteria were children diagnosed with septic shock according to the 2005 Surviving Sepsis Campaign (SSC) criteria, aged >30 days-18 years, who were followed up for 72h after resuscitation. The measured variables such as cardiac index (CI), systemic vascular resistance index (SVRI), stroke volume index (SVI) were obtained from ultrasonic cardiac output monitor (USCOM). Blood gas and lactate were obtained from laboratory findings. Heart rate, pulse strength, extremity temperature, mean arterial pressure (MAP), systolic blood pressure (SBP), capillary refill time (CRT), Glasgow coma scale (GCS), and diuretic used were obtained from hemodynamic monitoring tools. Survival outcomes of post-resuscitation pediatric septic shock patients were noted. Results There was a significant correlation between the outcomes of the pediatric septic shock patients 72h after fluid resuscitation and clinical, macrocirculatory hemodynamic, and microcirculatory laboratory parameters. After the 6th hour of observation, strong pulse was predictive of survival, with 88.2% area under the curve (AUC). At the 12th hour of observation, MAP >50th percentile for age was predictive of survival, with 94% AUC. Conclusion For pediatric patients with septic shock, the treatment target in the first 6 hours is to improve strength of pulse, and that in the first 12 hours is to improve MAP >50th percentile for age to limit mortality.